Toward an ecology of transfiguration orthodox Christian perspectives on environment, nature, and creation - Chryssavgis, John; Foltz, Bruce V. (Orthodox Christianity and contemporary thought., 2013)
"Can Orthodox Christianity offer unique spiritual resources especially suited to the environmental concerns of today? This book makes the case that yes, it can. In addition to being the first substantial and comprehensive collection of essays, in any language, to address environmental issues from the Orthodox point of view, this volume with contributions from the most highly influential theologians and philosophers in contemporary world Orthodoxy will engage a wide audience, in academic as well as popular circles--resonating not only with Orthodox audiences but with all those in search of a fresh approach to environmental theory and ethics that can bring the resources of ancient spirituality to bear on modern challenges"--